IDDAH PEREMPUAN HAMIL KARENA ZINA ( Studi Kasus Pasal 53 Kompilasi Hukum Islam) - Distiliana, Distiliana (Faculty of Law, University of Palembang, 2024)
The iddah period is the waiting period for a woman who has been divorced by her husband, both dead divorced and live divorced in order to find out whether the woman is pregnant or not. To be clear, the biological father of the baby, in reality, women become pregnant not only because the result of a legal marriage can also occur as a result of adultery. Good adultery. This study aims to determine the iddah of pregnant women due to zina in the case study of Article 53 of the Compilation of Islamic Law. This research includes qualitative research, namely literature research, which is the object of study in the form of library data, namely supporting books relevant to the research, namely Iddah pregnant women due to adultery case study article 53 Compilation of Islamic law, articles, mass media (newspapers), previous research reports and so on. The technique used is through three ways, namely collecting research materials, reviewing and analyzing the results of various readings. The Regulation of the Compilation of Islamic Law article 53 paragraphs 1, 2 and 3 concerning the marriage of pregnant women out of wedlock can be interpreted that, pregnant women due to adultery are not obliged to the iddah period for her The iddah period is a mandatory waiting period for women who are rejected by their husbands either divorced alive or divorced dead. The period of iddah of a pregnant woman due to zina refers to article 53 on marriage of pregnant women in paragraphs 1, 2 and 3 so there is no period for her to be iddah and the woman may marry the man who impregnated her even if the baby in the womb has not been born.